2019
DOI: 10.1108/caer-03-2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Estimating market power in the Chinese pork-packing industry: a structural approach

Abstract: Purpose The purpose of this paper is to investigate market power in the Chinese pork supply chain. The authors aim to explain why a steady rise in prices is observed in the sector, apart from existing evidence on incomplete/asymmetric cost pass-through and concerns of growing concentration and consolidation in the sector. Design/methodology/approach This study uses a new empirical industrial organization model for both oligopoly and oligopsony power to measure the degree of market power exerted on consumers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the first one, market structures and outcomes are viewed from an industrial organization perspective and analyzed accordingly by identifying the market and its structure, before using econometric techniques to measure the market power based on market observations benchmarked against an hypothetical efficient market outcome [20,21]. Most studies that have applied such methods to measure market power in meat markets are from the U.S. [22][23][24][25], while several studies are from other countries, such as Canada [26], Austria [19], Japan [27], Germany [28], and China [29]. The OECD (2006) provides empirical evidence for Canada, the Czech Republic, Japan, and the Netherlands [30].…”
Section: Literaturementioning
confidence: 99%
“…In the first one, market structures and outcomes are viewed from an industrial organization perspective and analyzed accordingly by identifying the market and its structure, before using econometric techniques to measure the market power based on market observations benchmarked against an hypothetical efficient market outcome [20,21]. Most studies that have applied such methods to measure market power in meat markets are from the U.S. [22][23][24][25], while several studies are from other countries, such as Canada [26], Austria [19], Japan [27], Germany [28], and China [29]. The OECD (2006) provides empirical evidence for Canada, the Czech Republic, Japan, and the Netherlands [30].…”
Section: Literaturementioning
confidence: 99%
“…On the contrary, the rural development in the middle and western regions is backward, a lot of financial support is needed in the process of rural revitalization, there is more room for farmers to increase their income rapidly and the improvement effect of increasing the level of rural credit input on the urban-rural income gap is more obvious. At the same time, considering the heterogeneity of regional development and the similarity of the average development level, this paper divides the samples of 31 provinces in China by "dichotomy" [7] so as to identify whether there is heterogeneity between regions (Lan and Wang, 2019). The empirical analysis of this article is mainly completed by Stata 15.0.…”
Section: Rural Credit Inputmentioning
confidence: 99%
“…As neither existing competition laws or voluntary codes of conduct sufficiently address these issues, the ACCC recommended that a mandatory code of conduct should be introduced. 27 Across the different market studies reviewed in Annex B, several indicated concerns around competitive conditions. Eastern European countries in particular highlighted the issue of unfair trading practices along the food chain.…”
Section: Sectoral Investigations By Competition Authoritiesmentioning
confidence: 99%
“…The discussion here is limited to those studies conducted by competition authorities, as these often have more powerful investigative tools at their disposal 26. See https://www.accc.gov.au/focus-areas/inquiries/dairy-inquiry-0 (accessed 25 September 2019) 27. It is worth pointing out that the ACCC study did not find clear evidence of processor buyer power or collusion between processors.…”
mentioning
confidence: 99%